Edukasi Penggunaan Air Bersih dalam Mendukung Kesehatan Lingkungan Masyarakat di Kelurahan Mariana Kabupaten Banyuasin I - Anggi Nidya Sari; Andi Herius; Kiki Rizky Amalia; Rizky Franchitika; Arif Roziqin; Rahmat Hakiki (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
This community service activity was carried out with the aim of increasing public awareness in Kelurahan Mariana regarding the importance of using clean water. The activity took the form of community outreach and education concerning clean water, the requirements of clean water and the benefits of using clean water. The implementation of this socialization program was expected to provide the community with greater insight into water that is safe and suitable for daily use and consumption. In additioan to the educational sessions, a demonstration was also conducted on the use of a simple clean water filtration device that can be independently made by the community in their respective homes. By increasing public knowledge about the importance of clean water usage, it is expected that a healthier environment can be created and the spread of diseases can be reduced. The results of this community service activity showed that the community gained a better understanding of the importance of using clean water and increased public awarness to continuously strive for the use of clean water in their daily activities.